The relationship between motivations of an employees and job performance that implemented in Universiti Kebangsaan Malaysia (UKM) / Nurul Ain Nazaruddin - Nazaruddin, Nurul Ain (Faculty of Business and Management, 2010)
Motivation is main factors of the employees that lead to job performance at their organization. There are three types of motivation which is achievement, affiliation and power motivations. High motivation among employees, outstanding ability, good organizational climate and infrastructure, excellent leadership by head of department, productivity and good relationship among staff can provide increment in performance among employees. The aim of this study to investigate the relationship of the independent variables: achievement motivation, affiliation motivation and power motivation toward job performance that implemented in Universiti Kebangsaan Malaysia, Bangi, Selangor. Data were collected from 40 respondents and they are randomly selected from Registrar Department at UKM, Bangi. The study revealed the motivation factors that contribute to the job performance. The descriptive statistic was use to discuss on the profile of respondents, Cronbach’s Alpha was used to test the reliability coefficient all independent variables and dependent variables while Spearman’s Correlation matrix was use to see the strength of interrelated that present independent and dependent variables among all mentioned. Results obtained from the Spearman’s correlation analysis revealed that the three motivation factors which are achievement, affiliation and power were strongly related to job performance. Achievement motivation was moderately positive related to job performance and affiliation motivation was also found to be positive. Power motivation also show the positive result but low related to job performance. The ranking show achievement motivation show the highest ranking in influencing job performance in UKM and it was followed by affiliation motivation and power motivation Finally, the study recommends among other things that the organizations should provide a proper training in focuses more on the development of the individual, organization also may use the technology more widely in interacting with their staff and sharing information among them and they also should willingly seek for challenges to improve their motivation and also performance in organizational to enable them to perform their job better.